The Correlation Between Crystal Phase and Acidity in Nickel Doped Zinc Fluoride Solid - Ummi Nazhiroh; Irmina Kris Murwani (Akta Kimia Indonesia, 2022)
Nickel-doped zinc fluoride (Zn1‑xNixF2) with x= 0; 0.025; 0.050; 0.075; 0.100 and 0.150 were synthesized from zinc acetate as precursors. Solid materials were prepared by the fluorolytic sol gel method. The resulting solid materials were characterized by XRD and FTIR. The XRD characterization of the samples showed that there were characteristic peaks of zinc fluoride, zinc oxide and zinc hydrogen fluoride. The IR characterization spectrum showed the presence of Zn-F, Zn-O and -OH bonds in the samples. Pyridine adsorbed FTIR technique explains that the material has Lewis and Brønsted acidity. The acidity site in the solid were influenced by the Zn-O and Ni-O bonds in the catalyst.